Protective Effects of Thymoquinone on Endothelial Cell Dysfunction in Hypercholesterolemia - Wardani, Giftania (Universitas Airlangga, 2024)
Background: Increased reactive oxygen species (ROS) have been implicated as important mechanisms that contribute to endothelial dysfunction (ED). The administration of thymoquinone in animal models significantly inhibits ROS production. Purpose: The protective effects of thymoquinone on endothelial cell dysfunction were studied in cholesterol-fed rabbits. Thirty rabbits were randomly divided into five groups. Methods: The negative control group was fed a standard diet, the positive control group was fed the same diet with 2 % cholesterol, the Thymoquinone group was fed the same diet with 2 % cholesterol and Thymoquinone 100 mg/Kg BW/day, 200 mg/Kg BW/day or 400 mg/Kg BW/day. Results: The cholesterol-rich diet significantly increased Malondialdehyde (MDA) in the aortic blood vessels, as reflected by Thiobarbituric Acid-Reactive Substances (TBARS), inhibited endothelium-dependent vascular relaxations to acetylcholine and decrease cyclic GMP were compared with vessels from normal rabbits (negative control). In cholesterol-fed rabbits, Thymoquinone treatment decreased MDA in plasma production, improved endothelium-dependent relaxations to acetylcholine and increase cyclic GMP production. Conclusion: These results suggest that dietary treatment of rabbits with thymoquinone may prevent superoxide anion (O2-) induced inactivation of endothelium-dependent relaxing factor (EDRF), improve the endothelium-dependent relaxation to acetylcholine in the aortic blood vessels, and increase cyclic GMP content in aortic of cholesterol-fed rabbits.